Advances in the chronological sequence of chiloe interior seas, western Patagonia: San Juan 1, Tauco 1 and 2 archaeological sites Avances en la secuencia cronológica del mar interior de chiloé, Patagonia occidental: Sitios arqueológicos San Juan 1, Tauco 1 y 2 - Reyes, Omar; Belmar, Carolina; San Roman Bontes, Manuel Julio; Morello Repetto, Flavia; Urbina, Ximena (My University, 2020)
As part of our research in the Chiloe archipelago, new contextual and chronological data are presented from three archaeological sites recorded on the east central coast of Chiloe Island. The described contexts and their chronology review occupations from the Middle and Late Holocene, and reflect the continuity of marine hunting and gathering traditions.
Keywords: chiloé; marine hunter-gatherers; middleand late holocene; western patagonian channels